A Historical Approach to the Mirror Neuron System - Palacios-Sánchez, Leonardo; Botía, Inés; Palacios-Espinosa, Ximena (Iatreia)
Introduction: Three decades after the discovery of mirror neurons (MN), interest in understanding their function as a system persists, and their impact on neuroscience, biology, medicine, and psychology continues to consolidate. Advances in mirror mechanism research have allowed for new ways of thinking about how one's own actions are generated and how those of others are interpreted. Objectives: To review the historical background of the MN system from its discovery to the present. Methods: A review of scientific literature published in databases was conducted, spanning from the discovery of MN in 1992 to 2023. Results: Findings on MN functions have led to understanding both positive aspects of human and non-human relationships, as well as certain mental health disorders. Conclusions: Research in this field could be promising for the development of prosocial behaviors that promote healthy coexistence in various settings. The initial enthusiasm manifested with the discovery of MN has been progressively nuanced, giving rise to a functional, neuroscientific perspective that requires more evidence on its therapeutic utility and applicability in areas of knowledge beyond health sciences.